2022
DOI: 10.3389/fendo.2022.848728
|View full text |Cite
|
Sign up to set email alerts
|

Determination of the Interaction and Pharmacological Modulation of MCHR1 Signaling by the C-Terminus of MRAP2 Protein

Abstract: Melanin concentrating hormone (MCH), an orexigenic neuropeptide, is primarily secreted by the hypothalamus and acts on its receptor, the melanin-concentrating hormone receptor 1 (MCHR1), to regulate appetite and energy homeostasis. The Melanocortin Receptor Accessory Protein 2 (MRAP2), a small single transmembrane protein broadly expressed in multiple tissues, has been defined as a vital endocrine modulator of five melanocortin receptors (MC1R–MC5R) and several other GPCRs in the regulation of central neuronal… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…MRAP2 prevents ghrelin‐stimulated GHSR1a phosphorylation to alter GHSR1a signaling and inhibit the recruitment of β ‐arrestin. [ 124 ] In addition, MRAP2 protein interacts with melanin‐concentrating hormone receptor 1 (MCHR1) to regulate appetite and energy homeostasis [ 125 ] and also selectively interacts with the growth inhibitory hormone receptor (SSTR) to regulate exocrine secretion, inhibit endogenous cell proliferation, etc. [ 126 ]…”
Section: The Mc4r Signaling Pathwaymentioning
confidence: 99%
“…MRAP2 prevents ghrelin‐stimulated GHSR1a phosphorylation to alter GHSR1a signaling and inhibit the recruitment of β ‐arrestin. [ 124 ] In addition, MRAP2 protein interacts with melanin‐concentrating hormone receptor 1 (MCHR1) to regulate appetite and energy homeostasis [ 125 ] and also selectively interacts with the growth inhibitory hormone receptor (SSTR) to regulate exocrine secretion, inhibit endogenous cell proliferation, etc. [ 126 ]…”
Section: The Mc4r Signaling Pathwaymentioning
confidence: 99%
“…Therefore, whether the MRAP family could regulate other GPCR signaling attracted much attention for all melanocortin communities. A few evidence have shown that MRAP proteins could regulate the signaling and activity of additional non-melanocortin GPCRs, such as orexin receptor 1 (OX1R), GHSR1a, PKR1, somatostatin receptors (SSTRs), and melanin-concentrating hormone receptor 1 (MCHR1) ( Chaly et al, 2016 ; Rouault et al, 2017 ; Srisai et al, 2017 ; Wang et al, 2022 b, 2022 c). It is noteworthy that these few reported GPCRs share similarities in terms of expressional distribution with MRAP2.…”
Section: The New Exploration Of the Mrap Familymentioning
confidence: 99%
“…In mice, global ablation of PK2 or PKR1 leads to obesity [6]. The activation of PKRs is modulated by melanocortin receptor accessory protein 2 (MRAP2), a membrane protein that binds several G protein-coupled receptors (GPCRs) involved in the control of energy homeostasis [21][22][23][24][25][26][27][28]. The anorexigenic effect of PK2 through the binding of PKR1 is enhanced in MRAP2 knock-out (KO) mice compared to wild-type (WT) mice, demonstrating the inhibitory role of MRAP2 on PKR1 in vivo [29].…”
Section: Introductionmentioning
confidence: 99%